2021
DOI: 10.21608/ejchem.2021.50016.3036
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Iron, Zinc and Lead by Azolla pinnata and Lemna minor and activity in contaminated water

Abstract: In this study, two aquatic macrophytes namely, Azolla pinnata and Lemna minor are floating plants were obtained from Agric. Microbial Dept., Soils, Water and Environment Research Institute (SWERI), Agric. Res. Center (ARC), Giza, Egypt and used to some heavy metal such as Iron, Zinc and lead This study reported the ability of two aquatic plants (A. pinnata and L. minor) to remove Iron, Zinc and lead from aqueous solutions FeSO4.7H2O, ZnSo4.7H2O and C4H6O4Pb.3H2O of four different initial concentrations (0-100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Lemna minor is one of the ideal aquatic plants that can be used as a phytoremediator of various pollutants such as removing methylene blue (Imron et al, 2021). The maximum removal of Fe,Zn (88.18,84.63 %) by L. minor at 100 ppm initial metal concentration after 20 days of incubation (Mohamed et al, 2021) Many aquatic plants were reported that they can survive, grow and reproduce in contaminated environments. Metal-resistant organisms minimize the biological effects of metals in the soil or reduce the proteins to transport and absorb metals.…”
Section: Introductionmentioning
confidence: 99%
“…Lemna minor is one of the ideal aquatic plants that can be used as a phytoremediator of various pollutants such as removing methylene blue (Imron et al, 2021). The maximum removal of Fe,Zn (88.18,84.63 %) by L. minor at 100 ppm initial metal concentration after 20 days of incubation (Mohamed et al, 2021) Many aquatic plants were reported that they can survive, grow and reproduce in contaminated environments. Metal-resistant organisms minimize the biological effects of metals in the soil or reduce the proteins to transport and absorb metals.…”
Section: Introductionmentioning
confidence: 99%
“…The high tissue uptake and moderate transfer factor indicate tolerance of P. stratiotes to lead (Pb) stress at the concentrations used and its phytoremediation potentials in the present study. In a similar study using some floating aquatic plants (Lemna minor and Azolla pinnata), Mohamed et al (2021) observed less efficient removal of lead by Lemna minor compared to Azolla pinnata. A reduction in plant biomass indicates a disruption of the physiological mechanisms of the plant.…”
Section: Discussionmentioning
confidence: 81%
“…Low biomass indicates disruption of metabolic and photosynthetic activities exerted by heavy metal stress (Das et al, 2014). Similarly, Mohamed et al (2021) reported that L. minor has low biomass for some heavy metals including lead during 20 days of incubation time. The tissue retention and concentrations tested in this study were contrary to the findings of Mohamed et al (2021) that observed L. minor exposed to 25 mg/L lead for 20 days of incubation, which recorded more accumulation rate compared to other higher concentrations; 50 mg/L and 100 mg/L.…”
Section: Discussionmentioning
confidence: 86%